Microplastics and cadmium pollution in Chinese sweet potato fields - Shi, Liang; Xu, Yuan; Chen, Zanming; Liu, Binhao; Hou, Yanan; Li, Jianmin; Dang, Fei; Wang, Yujun; Shen, Zhenguo; Yang, Jinghui; Chen, Yahua (Frontiers in Sustainable Food Systems, 2024)
Context and background: Microplastic (MP) and heavy metal (HM) coexist in farmland of China. Motivation: It still remains unclear their exposure levels and distribution in sweet potato fields. Hypothesis: Polyethylene (PE) or polyamide (PA) is the main MP pollutant in contaminated sweet potato sites and the MP abundance in low latitude and eastern areas are highest. Methods: In this study, saturated NaCl solution, stereo microscope, Fourier transform infrared spectrometer, and Electrothermal digester are used for the extraction, observation, identification of MPs and analysis of Cd elements in soil, respectively. Results: Here, we found an average MP level at 112,400 items/kg in 30 sweet potato field sites based on the items in 5 g soil and the magnification (200x), and the maximum abundance is 197,153 items/kg in Laiyang city, Shandong province by field survey. The distribution characteristics of MPs are middle latitude areas < low latitude areas, and eastern areas > central areas.Most MPs are of the fragment and film shape, which account for 47.96% and 40.22% respectively. In order to detect MP polymers in three cities named "Liancheng", "Huanggang" and "Laiyang" with different degrees of development, a laser infrared imaging system as a novel instrument is used to explore the MPs which size is above 10 μm. Conclusions: The results showed that PA is the main MP pollutant in contaminated sweet potato sites, and soil texture, planting time, and urbanization process may be the main factors affecting MP distribution. The average cadmium (Cd) concentrations in 215 field sites is 0.15 mg/kg, and the local Cd pollution is existing, but the overall pollution is low. In addition, Cd concentration was negatively correlated with MP abundance. This study reveals the status of MP, and also Cd 3 pollution in sweet potato fields, which provide a theoretical basis for the safe production and utilization of sweet potato fields.